The theory and application of heated films for the measurement of skin friction - Mathews, J. (Cranfield University, 1985)
The use of hot surface films for measuring skin friction is examined. It is shown that all existing theories, which neglect heat conduction within the substrate, are inadequate in predicting the variation of heat loss from the film with skin friction. A more physically realistic theory is presented which accounts for the conductive and convective heat transfer into the flow and also heat conduction within the substrate. This leads to a more general relationship between skin friction and heat loss from the film. Experiments conducted in flat plate laminar and turbulent boundary layer flow show that this relationship is more accurate than previous forms. The time and temperature dependence of the heat loss from the hot film are also explored theoretically and experi- mentally. The effect of surface misalignment of the film is shown to alter significantly the convective heat transfer. This effect is more pronounced in laminar flow than in turbulent flow. Using a glue-on hot film probe, calibrations relating the heat loss to skin friction were found to be different in laminar and turbulent flow. An experimental operating procedure for the use of hot surface films for measuring skin friction is proposed which significantly increases the accuracy of the technique.